A Humanist’s Legacy in Medical Informatics: Visions and Accomplishments of Professor Jean-Raoul Scherrer - Geissbühler, A.; Lovis, C.; Spahni, S.; Appel, R. D.; Ratib, O.; Boyer, C.; Hochstrasser, D. F.; Baud, R. (Methods of Information in Medicine, 2002)
Objective: To report about the work of Prof. Jean-Raoul Scherrer, and show how his humanist vision, his medical skills and his scientific background have enabled and shaped the development of medical informatics over the last 30 years.Results: Starting with the mainframe-based patient-centered hospital information system DIOGENE in the 70s, Prof. Scherrer developed, implemented and evolved innovative concepts of man-machine interfaces, distributed and federated environments, leading the way with information systems that obstinately focused on the support of care providers and patients. Through a rigorous design of terminologies and ontologies, the DIOGENE data would then serve as a basis for the development of clinical research, data mining, and lead to innovative natural language processing techniques. In parallel, Prof. Scherrer supported the development of medical image management, ranging from a distributed picture archiving and communication systems (PACS) to molecular imaging of protein electrophoreses. Recognizing the need for improving the quality and trustworthiness of medical information on the Web, Prof. Scherrer created the Health-On-the-Net (HON) foundation.Conclusions: These achievements, made possible thanks to his visionary mind, deep humanism, creativity, generosity and determination, have made of Prof. Scherrer a true pioneer and leader of the human-centered, patient-oriented application of information technology for improving healthcare.
Keywords: Hospital information systems; bioinformatics; e-health